2013
DOI: 10.1111/nep.12041
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual coping, religiosity and quality of life: A study on Muslim patients undergoing haemodialysis

Abstract: Spiritual resources may contribute to better quality of life and health status among haemodialysis patients. Further longitudinal studies are needed to determine whether these associations are causal and the direction of effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
73
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 37 publications
7
73
0
3
Order By: Relevance
“…Observational, national and international studies conducted with patients with chronic kidney disease receiving peritoneal dialysis and hemodialysis showed similar results. (6,7,(13)(14)(15)(16) Those of the female gender had a better perception of HRQOL in the dimension "quality of social interaction," but without a statistically significant difference. This finding is consistent with the results of a survey conducted with 100 patients receiving hemodialysis in Saudi Arabia, which identified that male gender, older age and duration of treatment emerged as predictors of a lower quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Observational, national and international studies conducted with patients with chronic kidney disease receiving peritoneal dialysis and hemodialysis showed similar results. (6,7,(13)(14)(15)(16) Those of the female gender had a better perception of HRQOL in the dimension "quality of social interaction," but without a statistically significant difference. This finding is consistent with the results of a survey conducted with 100 patients receiving hemodialysis in Saudi Arabia, which identified that male gender, older age and duration of treatment emerged as predictors of a lower quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a study of 362 patients on hemodialysis, developed in Iran, which reported better HRQOL in patients with a partner due to higher social support. (16) With regard to education, participants with a higher level of education had better HRQOL than subjects with an incomplete elementary education. This finding is similar to other studies of a cross-sectional design, developed in the capital of São Luís (n=306), Madrid (n=61) and Riyadh (n=100), in which the respondents with chronic disease receiving dialysis, and who had a higher educational level, reported having greater access to information, better economic conditions, and better capacity to evaluate traumatic phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esto puede significar que las personas con ERC, a pesar de presentar interferencia del dolor en sus actividades, continúan satisfechas con la vida en general. Existieron otras variables moderadoras como la espiritualidad, o sea, que las personas más espirituales enfrentan mejor el dolor crónico, lo que ayuda a preservar la calidad de vida relacionada con la salud (39)(40)(41).…”
Section: Discussionunclassified